2020
DOI: 10.1021/acs.est.9b06433
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of East Asian Emissions of CFC-11 Using Atmospheric Observations in Taiwan

Abstract: Recent findings of an unexpected slowdown in the decline of CFC-11 mixing ratios in the atmosphere have led to the conclusion that global CFC-11 emissions have increased over the past decade and have been attributed in part to eastern China. This study independently assesses these findings by evaluating enhancements of CFC-11 mixing ratios in air samples collected in Taiwan between 2014 and 2018. Using the NAME (Numerical Atmospheric Modeling Environment) particle dispersion model, we find the likely source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
(131 reference statements)
2
18
0
Order By: Relevance
“…Until now, most studies of CFC changes are based on model simulations, which sometimes show large differences in the results among each other and with observations. Furthermore, the CFC monitoring network does not have high enough spatial resolution currently, so that the observational data used in models has to come from monitoring stations in adjacent regions or countries [8,14,20]. Therefore, the conclusion of increasing CFCs emissions in Eastern China remains uncertain and lacks further solid evidence from field measurements [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, most studies of CFC changes are based on model simulations, which sometimes show large differences in the results among each other and with observations. Furthermore, the CFC monitoring network does not have high enough spatial resolution currently, so that the observational data used in models has to come from monitoring stations in adjacent regions or countries [8,14,20]. Therefore, the conclusion of increasing CFCs emissions in Eastern China remains uncertain and lacks further solid evidence from field measurements [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the CFC monitoring network does not have high enough spatial resolution currently, so that the observational data used in models has to come from monitoring stations in adjacent regions or countries [8,14,20]. Therefore, the conclusion of increasing CFCs emissions in Eastern China remains uncertain and lacks further solid evidence from field measurements [20]. In this study, field samples at urban and rural residential sites, industrial areas, and municipal solid waste (MSW) landfills were collected in Shandong Province of the Eastern China, where densely industrial estates are distributed, during the period of October-December, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies highlight the need for continued, careful monitoring of CFCs. Montzka et al (2018) found evidence for a recently emerged source of atmospheric CFC-11, with subsequent studies tracing these emissions largely to north-east China (Rigby et al, 2019;Adcock et al, 2020). In addition, Adcock et al (2018) found increasing mole fractions of CFC-113a.…”
Section: Introductionmentioning
confidence: 85%
“…However, a large increase in global CFC-11 emissions from 2012-2017 was discovered (Montzka et al, 2018;Rigby et al, 2019;Montzka et al, 2021), suggesting illicit CFC-11 production despite the global ban on production and consumption under the MP beginning in 2010. This surprisingly large increase in CFC-11 emissions attracted great attention from scientists, policy makers, and industrial experts around the world (Montzka et al, 2018;Rigby et al, 2019;Dhomse et al, 2019;Ray et al, 2020;Adcock et al, 2020;Keeble et al, 2020;Chen et al, 2020), who sought information to enable rapid mitigation of the unexpectedly enhanced CFC-11 emissions and ensure no significant delay in the recovery of stratospheric ozone. Despite the international effort to understand the origin of this large global emission increase in CFC-11, only a portion of the emission rise (60 ± 40 %) could be explained by emission increases from eastern mainland China (Rigby et al, 2019;Adcock et al, 2020;Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%